Correlation between Neutrophil to Monocyte Ratio, C-Reactive Protein, and D-dimer Levels among COVID-19 Patients - Melkior Krisna Arondaya; Dwi Retnoningrum; Banundari Rachmawati; Santoso Jaeri (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
COVID-19 is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) and leads to various clinical manifestations. This condition can cause inflammation and cardiovascular disease that can result in increased Neutrophil-to-Monocyte Ratio (NMR), C-Reactive Protein (CRP), and D-dimer. The correlation between variables needs further investigation that can be a reference. This study aimed to analyze the correlation between NMR and CRP also NMR and D-dimer in COVID-19 patients with moderate dan severe illness. The research was an observational analytical study with a cross-sectional design on 40 subjects. Data were secondary data from COVID-19 patient’s medical records in RSND Semarang. This study was carried out from April to September 2021. Correlation analysis using the Spearman Rank test with p<0.05 was considered significant. The Mean of NMR, CRP, and D-dimer was 16.69±10.65, 113.94±70.42 mg/L, and 1.72±2.35 mg/L, respectively. There was a weak positive correlation between NMR and CRP (p=0.023 and r=0.358) and there was no correlation between NMR and D-dimer (p=0.638 and r=0.077). It was expected that this knowledge about the correlation between NMR and CRP and D-dimer can help healthcare providers in planning therapy and preventing complications that may occur due to CRP and D-dimer increase.